Modulation of Adult Hippocampal Neurogenesis by Early-Life Environmental Challenges Triggering Immune Activation - Ksenia Musaelyan; Martin Egeland; Cathy Fernandes; Carmine M. Pariante; Patricia A. Zunszain; Sandrine Thuret (Neural Plasticity)
The immune system plays an important role in the communication between the human body and the environment, in early development as well as in adulthood. Per se, research has shown that factors such as maternal stress and nutrition as well as maternal infections can activate the immune system in the infant. A rising number of research studies have shown that activation of the immune system in early life can augment the risk of some psychiatric disorders in adulthood, such as schizophrenia and depression. The mechanisms of such a developmental programming effect are unknown; however some preliminary evidence is emerging in the literature, which suggests that adult hippocampal neurogenesis may be involved. A growing number of studies have shown that pre- and postnatal exposure to an inflammatory stimulus can modulate the number of proliferating and differentiating neural progenitors in the adult hippocampus, and this can have an effect on behaviours of relevance to psychiatric disorders. This review provides a summary of these studies and highlights the evidence supporting a neurogenic hypothesis of immune developmental programming.